Graffito of the Scribes of the Royal Necropolis of the 21st Dynasty from the Hatshepsut Temple at Deir el-Bahari - Barwik, Mirosław (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
A hieratic graffito from the temple of Queen Hatshepsut refers to the names of the members of the well-known family of the scribes of the royal necropolis, descendants of the scribe Tuthmosis and his son Butehamun. This graffito can be dated to the period of the early 21st Dynasty, as at least three of the sons of Butehamun are mentioned here, alongside one of his grandsons by the name Meniunefer (III).